RELATIONSHIP BETWEEN CHARACTERISTIC PATIENT WITH RECURRENT CORONARY HEART DISEASE: Hubungan Karakteristik Pasien dengan Penyakit Jantung Koroner Berulang - Haryuni, Sri; Afiani, Nurma; Wahid, Abdurahman; Ana Anggraini, Novita; Perdana Sulistyoning Suharto, Idola; Jayani, Indah (Jurnal Berkala Epidemiologi, 2025)
Background:  Recurrent coronary heart disease (CHD) increases the risk of complications and mortality among hospitalized patients. Previous studies report a 58% mortality rate within one year of treatment and a 30% recurrence rate in CHD patients. Purpose:  This study aimed to examine the relationship between patient characteristics and CHD recurrence. Methods:  A retrospective quantitative study was conducted at Kediri City Regional Hospital. A total of 123 CHD patients were selected using proportional random sampling. Independent variables included age, gender, education, income, and knowledge, while the dependent variable was CHD recurrence. Data were analyzed using Chi-square tests and logistic regression. Results:  Bivariate analysis showed significant associations between age (p = 0.000) and knowledge (p = 0.01) with CHD recurrence. No significant associations were found for income (p = 0.373), gender (p = 0.194), or education level (p = 0.983). Multivariate analysis confirmed age (p = 0.000, OR = 8.426, 95% CI: 3.266–21.736) and knowledge (p = 0.017, OR = 2.984, 95% CI: 1.215–7.33) as significant predictors of CHD recurrence. Conclusions:  Older patients are at a significantly higher risk of CHD recurrence compared to younger ones. Additionally, patients with better knowledge about CHD are less likely to experience recurrence. These findings highlight the importance of age-specific and educational interventions in preventing CHD relapse.